THE EFFECTIVENESS OF COLLABORATIVE LEARNING ON THE MATHEMATICS LEARNING ACHIEVEMENT AMONG 8TH GRADE STUDENTS OF SMPN 1 AJANGALE , INDONESIA - Dian Nugraha; Kasmawati Kasmawati; Raihana Uzda (Universitas Brawijaya, 2020)
This research involved two classes to which achievement tests were administered. The initial achievement test aimed to assess students’ initial knowledge of mathematics, while the final test was carried out to evaluate students’ learning outcomes after treatment. The results of this study showed that experimental class obtained higher average final test score (84.70) than control class (80.44).The independent sample t test also showed a value lesser than alpha (0.012 <0.05). As a class, the improvement was also shown by proportion test results, in which zcount> ztable (2.50> 1.64). Regarding those results, the use of collaborative learning brought significant improvement in mathematics learning outcomes of 8th grade students of SMPN 1 Ajangale.